KLASIFIKASI DAERAH DAN PENGARUH SEKTOR EKONOMI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN GROBOGAN - Eka Sulistya Anggraeni; Niniek Imaningsih (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
This study aims to identify leading and non-leading economic sectors, analyze shifts in economic sectors, classify the position of Grobogan Regency within regional development typology, and measure the influence of basic sectors on regional economic growth. The methods used in this research include Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift Share, Klassen Typology, and simple linear regression. This is a quantitative study employing statistical data analysis to describe the regional economic conditions and dynamics. The data used are secondary data in the form of Gross Regional Domestic Product (GRDP) of Grobogan Regency and Central Java Province for the period 2019–2023, obtained from the publications of the Central Bureau of Statistics (BPS). The analysis results indicate that several basic sectors consistently contribute to economic growth, while some sectors have experienced a shift in their roles. Based on the Klassen Typology, Grobogan Regency is mostly classified within the quadrants of rapidly developing and underdeveloped regions. Furthermore, regression results show that basic sectors have a significant influence on regional economic growth. These findings can serve as a reference for more targeted and sector-based regional development planning.